Manufacturing Industry Growth Patterns and Analysis of Variables Affecting Value Added (Case Study: China, Malaysia, Thailand, Indonesia, and England 1998-2005) - Achmad Erwin Susandi (International Journal of Applied Finance and Business Studies, 2020)
The purpose of this research is to examine and understand the pattern of manufacture industry growth towards labor force absorption and also to examine and analyze variables that have influence towards manufacture industry value added in China, Malaysia, Thailand, Indonesia, and England in the year 1998–2005 and also to see if there is any significant disparity between each country for the manufacture industry value added. The analysis tool that used to answer the purpose of this research is kendal correlation test and data panel regression using country dummy. Result of analysis it can be concluded that proportionaly growth pattern increased labor force absorption only in Malaysia, while in England doesn't show a proportional pattern. Variables that influenced manufacture industry value added in monitoring country is foreign investment and export. Meanwhile the data panel regression using the country dummy showed that there are significant disparities between each country for the manufacture industry value added.